PERAN LITERASI DALAM MENINGKATKAN MINAT BACA SISWA KELAS VI DI SDN TALANG II - Wahyuni, Sri; Zakiyah, Nisa Azzahratus; Hidayat, Irfan Afri; Mas'odi, Mas'odi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2024)
The purpose of this study was to determine the role of literacy activities, obstacles and efforts made by the school in increasing elementary school students' interest in reading. This research is a qualitative research. The research subjects were the principal, teachers and students of grade VI of Talang II State Elementary School. Data collection techniques through interviews, observation and documentation. Based on the results of the research, it can be seen that 1) literacy activities play a role in increasing students' interest in reading, 2) obstacles in implementing literacy activities at school include the lack of infrastructure, the methods applied are less varied and the low discipline of students in the process of habituation of literacy activities, and 3) efforts made by the school in overcoming these obstacles are by providing socialization about literacy activities, adding facilities and holding competition activities as a means of active participation of students.